IMPLEMENTASI POHON LITERASI CERIA UNTUK PENGUATAN LITERASI BACA SISWA SDN 46 AMPENAN - Nelly Dwi Sabilia; Nur Ajura; Niki Herlina; Nanda Dini Cahyani; Muhammad Dani; Syafruddin Muhdar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the implementation of the Pohon Literasi Ceria media in strengthening reading literacy among elementary school students. This study was motivated by students’ low interest in reading due to the use of conventional and less interactive learning methods. The research employed a descriptive qualitative approach with a participatory model. The subjects consisted of 20 second-grade elementary school students. Data were collected through observation, interviews, and documentation. The implementation process included planning, implementation, and evaluation stages. During the implementation stage, students read books independently or with guidance, then wrote the results of their reading on “literacy leaves” and attached them to the Pohon Literasi Ceria media. The findings showed that this media was able to improve students’ reading interest, learning motivation, active participation, as well as their reading and simple writing skills. In addition, the media also helped enhance students’ communication skills through reading presentation activities. Although several obstacles were found, such as differences in reading abilities, limited learning time, and lack of varied reading materials, Pohon Literasi Ceria can still serve as an innovative learning medium for improving the quality of reading literacy learning in elementary schools.